Effect of freezing on microstructure and reconstitution of freeze-dried high solid hydrocolloid-based systems - Malik, N.; Gouseti, O.; Bakalis, S. (Elsevier, 2018)
Freeze-drying has been associated with high quality hydrocolloid-based products such as coffee. However, it is an expensive technique, and one way to reduce energy and water use is by drying concentrated systems. Controlling the ice crystal formation is important to produce final dried materials with desired microstructure and properties. This study presents the effect of freezing with and without temperature oscillations on the final microstructure and reconstitution of aerated and non-aerated freeze-dried concentrated (50 and 60% w/w) gum arabic and coffee systems. Samples were either frozen at -40 C or subjected to fluctuating temperatures between -40 and -20 C prior to drying. Thermal analysis of the systems showed lower nucleation and freezing temperatures for 50% compared to 60% solutions, as expected, and melting temperatures > -20 C. During drying, puffing of the material was observed, with appearance of a glass-like, puffed bottom layer, in particular for the 60% coffee frozen at -40 C. SEM micrographs revealed pores of dendritic, hexagonal, and circular shape, indicating voids produced by sublimation of ice crystals. Pore sizes were smaller (by 50%, of the order of 40ìm) for the 60%, than the 50% systems. Temperature fluctuations during freezing doubled the observed pore sizes and the apparent total porosity which effectively accelerated the dissolution kinetics. Aeration resulted in the appearance of air bubbles (diameter 200e1600 mm) that largely phase separated in gum arabic and resulted in faster rehydrating solids. This work demonstrates the potential of process design to control microstructural attributes and reconstitution properties of freeze-dried hydrocolloid-based products in systems with high solute concentrations.